Contribution in the diagnosis of ultrasonography perinephric pseudocyst uriniferous in a feline - case report - Santos, D. R. [UNESP]; Souza, P. M. [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Belotta, A. F. [UNESP]; Freitas, M. A. [UNESP]; Kairalla, L.; Brandão, Claudia Valeria Seullner [UNESP]; Zanuzzo, F. S. [UNESP]; Machado, Luiz Henrique de Araújo [UNESP] (Univ Federal Rural Pernambuco, 2011)
The renal pseudocysts are accumulations of fluid unilateral or bilateral perirenal location, contained in a capsule without epithelium, a characteristic that distinguishes them from true renal cysts. The capsule itself may have originated in the renal capsule or a localized inflammatory reaction. The nature of the fluid can vary, but the presence of ooze found the most common, but they are also called pseudocysts accumulations of urine, blood and lymph. The most frequently observed clinical sign is abdominal distention. However these nonspecific signs may be related to chronic kidney disease and azotemia that may develop before or after the formation of this lesion. The abdominal ultrasound is less invasive and allows you to diagnose this change more easily, also allowing the collection of fluid guided percutaneous and submit it to cytological, biochemical and bacteriological in order to obtain information about its nature. This paper aims to describe a case of perinephric pseudocyst in a cat uriniferous, highlighting the contribution ultrasound as a diagnostic method complementary quick and noninvasive, allowing evaluation of the architecture of the renal parenchyma, differentiation of cortex and spinal cord as well as detect changes in size and shape of it, aiming for better planning in clinical surgery.
Keywords: pseudocyst; perinephric; feline; ultrasound